Relationship Between Body Mass Index and Physical Condition of Endurance of Football Referees of PSSI, Rokan Hulu Regency, Zone I - Putra, Deri; Resdianto, Resdianto; Cahyani, Chayani (Universitas Majalengka, 2024)
The problem in this study is the physical condition which is an important aspect for a soccer referee in carrying out the task of leading a soccer match for 90 minutes. The dominant physical aspect of leading the match is closely related to endurance. In reality, the condition of the Referee in the PSSI soccer sport of RokanHulu Regency Zone I on average has a reduced physical fitness condition. This research is a correlational study that aims to determine the relationship between Body Mass Index and the physical condition of the endurance of the PSSI soccer referee Rokan Hulu Zone I. with license levels C3, C2, and C1. This study uses 2 variables, consisting of 1 independent variable and 1 dependent variable. The independent variable is Body Mass Index (X), while the dependent variable is Endurance (Y). Based on the results of the correlation test using Product moment correlation, it shows a significant value (r_xy = 29.62) so it can be said that Body mass index is related to referee endurance. From the results of this analysis, the correlation coefficient value is obtained as rcount = 29.62> r_ (table = 0.396) which means it has a solid relationship.